CLINICAL AND IMMUNOLOGICAL FEATURES OF KIDNEY TRANSPLANT RECIPIENTS WITH CYTOMEGALOVIRUS INFECTION MANIFESTATION IN THE EARLY POSTOPERATIVE PERIOD - L. V. Limareva; A. V. Kolsanov; A. A. Avdeeva; O. P. Danilchenko; W. V. Bogush (Вестник трансплантологии и искусственных органов)
Aim. To optimize the management of postoperative renal allograft recipients through the introduction of methods for predicting risk of manifestation of cytomegalovirus infection on the basis of a comprehensive assessment of the clinical and immunological status. Materials and methods. We retrospectively analyzed the medical records of 303 patients with end-stage renal disease, among them – were the recipients of renal allograft – 136, among whom 29 within 2 months after the operation had clinical signs of CMV infection. Assessable "CMV syndrome", laboratory evidence of CMV infection, the incidence of antigens (genes) of HLA A, B and DRB *1, calculated goodness of fit χ2 and relative risk RR, changes MCP-1 in urine. Results. In renal allograft recipients with clinical and laboratory evidence of CMV infection in the early postoperative period, significantly more (χ2 > 3,8) met antigen B35. A positive association with CMV infection was detected also for DRB1 * 08, B21, B22, B41, A24 (9), B51 (5), DRB1*14 and DRB1*15. Protective effects possessed antigens / alleles of genes A26 (10), B14, B38 (16) B61 (40) and DRB1*16. MCP-1 levels in this group of recipients were raised to 2174,7 ± 296,3 pg/ml with a strong negative correlation with the levels of urea and creatinine in serum (r = 0,9, p < 0.001). Conclusion. Immunological markers of risk manifestation of CMV infection in recipients of kidneys in the early postoperative period are: the carriage of В35 и В55,56(22), В49(21), В41, DRB1*08 и DRB1*15, an increase of levels of MCP-1 in urine without increasing the levels of urea and creatinine in the serum.